Risky behaviour of high school students - Milanović, Nedjeljko M. (Array, 2021)
This article presents the results of an empirical research aimed at examining and analysing the presence of high school students' risky behaviour. The sample consisted of 137 high school students from the Republic of Serbia. A descriptive method was applied, and techniques a survey questionnaire technique that was constructed for this research. The obtained research results show that a large number of respondents consume cigarettes and alcohol, while they started going out to nightclubs already during elementary school. As the most common reason for consuming cigarettes, high school students cited the influence of their peers. More than half of high school students stated that alcohol is usually consumed once a week and on weekends, while a third of the respondents stated that they very often and often run away from classes. The analysed results lead us to the conclusion that risky behaviour is present among high school students and that it is necessary to pay more attention to this topic not only theoretically, but also practically through the unified action of the family, the school and the local community and a positive focus on overcoming the behavioural problems of this young population.